A light in the darkness an anecdotal history of Doomadgee Mission : fifty-three years of faithful, fealess endeavour by Assembly missionaries - Akehurst, Vic (Selangor, Malaysia Market Intelligence, 2006)
Includes indexes.
Brethren writer
Keywords: Brethren movement -- missionary activity -- history -- Australia; Doomadgee Mission. -- history -- 20th century